The electrocardiogram in non-ischaemic-dilated cardiomyopathy. (26th April 2023) - Crescenzi, Cinzia; Silvetti, Elisa; Romeo, Fabiana; Martino, Annamaria; Bressi, Edoardo; Panattoni, Germana; Stefanini, Matteo; Stazi, Alessandra; Danza, Maria Ludovica; Rebecchi, Marco; Canestrelli, Stefano; Fedele, Elisa; et al.
Abstract: This article summarizes the main electrocardiogram (ECG) findings in dilated cardiomyopathy (DCM) patients. Recent reports are described in the great 'pot' of DCM peculiar ECG patterns that are typical of specific forms of DCM. Patients with late gadolinium enhancement on CMR, who are at greatest arrhythmic risk, have also distinctive ECG features. Future studies in large DCM populations should evaluate the diagnostic and prognostic value of the ECG.